THE STUDENTS' PERCEPTION OF USING DUOLINGO AS A LANGUAGE TOOL FOR LEARNING ENGLISH - Retno Lestari; Retno Lestari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: With the development of technology, students are more interested in digital learning that uses an internet connection that can be accessed anywhere and anytime. Duolingo app is one of the modern apps that facilitate language acquisition. Duolingo offers a model of English courses based on everyday life in a simpler way. In this application users can learn vocabulary and grammar, even this application provides a mixture of abilities in pronunciation, and word translation and provides activities to understand words from pictures, and others. Duolingo combines elements from audio visual questions in a fun way. With the gamification system offered, it can help to build interest in learning in a comfortable way and not get easily bored when learning.This study aims to determine the perception of students majoring in English towards the use of the Duolingo application as a language learning tool to learn English and to find out what aspects of language improve after using the Duolingo application as a language learning tool. The research design of this research is qualitative research. Participants in this study were 28 English students at the Universitas Islam Malang who had used the Duolingo application for more than 40 days. The data were collected by giving a questionnaire and interviewing the students.From the results of this study, most students are agreeing about the statement toward the use of the Duolingo application in their English learning. The results of the questionnaires and interviews obtained by the researcher explained that students agreed that the Duolingo application had many positive effects on students in language learning such as students becoming more motivated in learning and making students practice more and apply their language skills in everyday life. Also, some aspects of a language improve after using the Duolingo application, such as students knowing a lot of vocabulary and memorizing it easily, becoming better at grammar and pronunciation, and making it easier for students to improve their English language acquisition.Based on the finding of the study, it is addressed for future researchers. The researcher hopes that further research can examine with a larger sample and dig deeper into other topics related to the use of the Duolingo application and its implementation in English language teaching.Â keywords:Â Studentsâ€™ perception, Duolingo, language tool, learning English